2019
DOI: 10.1093/nar/gkz1128
|View full text |Cite
|
Sign up to set email alerts
|

mitoXplorer, a visual data mining platform to systematically analyze and visualize mitochondrial expression dynamics and mutations

Abstract: Abstract Mitochondria participate in metabolism and signaling. They adapt to the requirements of various cell types. Publicly available expression data permit to study expression dynamics of genes with mitochondrial function (mito-genes) in various cell types, conditions and organisms. Yet, we lack an easy way of extracting these data for mito-genes. Here, we introduce the visual data mining platform mitoXplorer, which integrates expression and mutation data of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 126 publications
0
50
1
Order By: Relevance
“…Gain of a chromosome was shown to cause genotoxic stress due to abnormal replication 3,19,20 , and we propose that this may be the reason for the accumulation of dsDNA in the cytosol of trisomic cells. The DNA may also originate from damaged mitochondria that are often found in trisomic cells 50 ; however, our data suggest rather a nuclear origin of the cytosolic DNA. Micronuclei arising from missegregation of chromosomes were previously reported to activate the cGAS-STING pathway and, subsequently, the NF-κB-mediated transcription [51][52][53] ; however, the used model trisomic cell lines do not missegregate chromosomes at a significantly higher rate than the parental diploids 20 .…”
Section: Discussioncontrasting
confidence: 52%
“…Gain of a chromosome was shown to cause genotoxic stress due to abnormal replication 3,19,20 , and we propose that this may be the reason for the accumulation of dsDNA in the cytosol of trisomic cells. The DNA may also originate from damaged mitochondria that are often found in trisomic cells 50 ; however, our data suggest rather a nuclear origin of the cytosolic DNA. Micronuclei arising from missegregation of chromosomes were previously reported to activate the cGAS-STING pathway and, subsequently, the NF-κB-mediated transcription [51][52][53] ; however, the used model trisomic cell lines do not missegregate chromosomes at a significantly higher rate than the parental diploids 20 .…”
Section: Discussioncontrasting
confidence: 52%
“…We hypothesize that Down syndrome cells upregulate the 3-MST protein through the regulation of mRNA stability, and/or through various transcriptional mechanisms that may become activated in response to the presence of the additional 21 st chromosome in the cells, and/or through post-translational mechanisms (i.e., inhibition of 3-MST protein degradation), and/or through an increased transport of 3-MST into the mitochondria. Indeed, prior studies have shown that Down syndrome cells have significant disturbances in transcriptional and protein degradation and processing mechanisms, as well as in mitochondrial protein accumulation [32][33][34][35]. The above hypotheses describe conceivable potential mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…We then used the MitoXplorer pipeline ( Yim et al, 2020 ) to quantify the representation of 38 distinct mitochondrial processes within the identified DEGs. As anticipated from abolished respiration, BJ ρ0 fibroblasts showed DEGs for 29 mitochondrial processes compared to native BJ fibroblasts, especially within oxidative phosphorylation, mitochondrial genome translation, and amino acid metabolism processes ( Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%